2009
DOI: 10.1021/ac900162c
|View full text |Cite
|
Sign up to set email alerts
|

Contributions by a Novel Edge Effect to the Permselectivity of an Electrosynthesized Polymer for Microbiosensor Applications

Abstract: Pt electrodes of different sizes (2 × 10 -5 -2 × 10 -2 cm 2 ) and geometries (disks and cylinders) were coated with the ultrathin non-conducting form of poly(o-phenylenediamine), PPD, using amperometric electrosynthesis. Analysis of the ascorbic acid (AA) and H 2 O 2 apparent permeabilities for these Pt/PPD sensors revealed that the PPD deposited near the electrode insulation (Teflon or glass edge) was not as effective as the bulk surface PPD for blocking AA access to the Pt substrate. This discovery impacts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 106 publications
4
40
0
Order By: Relevance
“…This approach is similar to previous flow-injection analysis studies where the ratio itself was used [53]. The apparent permeability is a relative, normalized measure of the analyte flux to the metal surface when the polymer coating is present, and this parameter has proved useful in comparing the properties of permselective polymers for biosensor applications [2,42,49].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This approach is similar to previous flow-injection analysis studies where the ratio itself was used [53]. The apparent permeability is a relative, normalized measure of the analyte flux to the metal surface when the polymer coating is present, and this parameter has proved useful in comparing the properties of permselective polymers for biosensor applications [2,42,49].…”
Section: Discussionmentioning
confidence: 96%
“…Factors involved include: the nature of the first electron transfer step [45]; following chemical reactions with unreacted and oxidized monomer [45,46]; subsequent oxidation of soluble products, surface deposition of insoluble oligomers, and possible further oxidation of deposited molecules [46][47][48]; effects of electrode geometry on PPD permeability [34,49]; pH and background electrolyte effects [46,[50][51][52]; and the influence of applied potential during the polymerization process [46,52]. Although detailed literature reports describe aspects of the optimization of PoPD electrosynthesis for different purposes [31,43,52], only one study has compared the effects of applied potential on the relative H 2 O 2 and AA permeability of PoPD for biosensor applications [53].…”
Section: Introductionmentioning
confidence: 99%
“…1)) of current vs. (enzyme-substrate affinity) of 7.7207±0.1 nA mM -1 value on account of its high I max (good enzyme loading) [45]. As the LRS is the most important parameter from an analytical perspective (sensitivity in the linear response region) as reported by [46] the most of the experiments described hereafter refer to this design: Naf/ Ag-rGO-CNTs /Glu-Tyr …”
Section: Discussionmentioning
confidence: 99%
“…McMahon et al [19] initially suggested that faster hemispherical monomer diffusion at disc electrodes occurred during electropolymerization, forming non-compact polymer structure when compared with a slower linear diffusion at cylindrical electrodes, could have been the cause of decreased selectivity of disc electrodes. Recently, Rothwell et al [48] reported that the higher permeability to AA at PPD-coated disc electrodes was primarily due to a novel insulation-related edge effect, which was more pronounced in disc-type electrodes than cylinders. In a previous study, it was shown that decreasing the polymerization potential for the formation of PPD at discs from 0.7 V to 0.4 V enhanced the selectivity of these electrodes [44].…”
Section: Pt D /Ppd-bsa/pea/pei/gluox/ppd-bsamentioning
confidence: 99%